Mobile Wireless Middleware, Operating Systems and Applications - Workshops Mobilware 2009 Workshops, Berlin, Germany, April 28-29, 2009, Revised Selected Papers - Hesselman, Cristian (Lecture Notes of the Institute for Computer Sciences, Social Informatics and Telecommunications Engineering,, 2009)
Software systems for wireless and mobile communications are a key component in pervasive computing and are crucial for the materialization of easy-to-use and intel- gent services that people can use ubiquitously. As indicated by its acronym (MOBILe Wireless MiddleWARE, Operating Systems, and Applications), these are the type of systems that form the topic of the MOBILWARE conferencing series. In particular, the goal of MOBILWARE is to provide a forum for researchers and practitioners to disseminate and discuss recent advances in software systems for wireless and mobile communications, ranging from work on communication middleware and operating systems to networking protocols and applications. For its second edition, held in Berlin in April 2009, the MOBILWARE Organizing Committee decided to add a full day of workshops on topics related to the main c- ference. Our goals were threefold: 1. Put together a high-quality workshop program consisting of a few focused wo- shops that would provide ample time for discussion, thus enabling presenters to quickly advance their work and workshop attendees to quickly get an idea of - going work in selected research areas. 2. Provide a more complete picture of ongoing work by not only including technical workshops, but also workshops on business and user aspects. We expected that this multi-viewpoint approach would be an added value as technology, business m- els, and user experiences are usually interrelated. 3. Create a breeding ground for submissions for MOBILWARE 2010 and beyond.